دراسة شيوع إنتان السبيل البولي عند الأطفال المحمومين تحت عمر5 سنوات - خوري, مها; ياسين, زينب; أسعد, سيما (Latakia University Journal -Medical Sciences Series, 2019)
Background : Urinary tract infection is one of the most common infectious diseases in children . Fever is a common symptom of urinary tract infection in children younger than 5 years, but little attention is paid to urinary infections as a cause of fever in this age group . Objective: The objective of the following study is to determine the prevalence of urinary tract infection in Febrile children under the age of 5 years, and to identify the most important pathogens leading to urinary tract infection . METHODS: A descriptive study of a series of cases (200 children) from the Tishreen University Hospital Emergency Advisors at the age (1month -5 year )during the year 2019-2018 with fever story ≥38 ⁰ without a clear reason for clinical examination , Without a story taking antibiotics in the previous 48 hours . A urine test was performed with urine culture to diagnose the presence of urinary tract infection in children . Results: The study sample included 200 children (60 males 30% - 140 females 70%). The prevalence of urinary tract infection was 44% in the study sample. The most cases were in the 5-2 age group with 66% of the urinary tract infections, which is higher in females, 77.3% with a difference of value with p-value = 0.02 . E. coli was the most common pathogen for urinary tract infection (63.6%) and was most noticeable in the 5-2 age group. Urinary symptoms were the most common clinical symptoms of urinary infection (30.7%), which is higher in the 5-2 age group. Gastrointestinal symptoms are highest in the 1 to 2-year age group with 25% of the clinical symptoms of urinary infection. CONCLUSIONS: The study shows that the prevalence of urinary infection in Febrile children under the age of 5 years is high, which requires the assessment of children within this age group from the urine, urine examination and transplantation and the development of appropriate treatment to avoid serious complications of urinary tract infection. مقدمة : يعتبر إنتان السبيل البولي واحد من أشيع الأمراض الإنتانية عند الأطفال .وتعتبر الحمى أحد الأعراض الشائعة لإنتان السبيل البولي عند الأطفال بعمر أقل من 5سنوات ,مع ذلك يتم توجيه القليل من الإهتمام للإنتانات البولية كسبب للحمى عند هذه الفئة العمرية . الهدف :الهدف من الدراسة التالية هو تحديد شيوع إنتان السبيل البولي عند الأطفال المحمومين تحت عمر5سنوات , وتحديد أهم العوامل الممرضة المسببة لإنتان السبيل البولي . طريقة البحث : دراسة وصفية Descriptive Study(case series) لسلسلة من الحالات (200 طفل ) من مراجعي إسعاف مشفى تشرين الجامعي بعمر ( 1شهر- 5سنوات ) خلال عام 2019 -2018 بقصة حمى≥ 38 ⁰ بدون وجود سبب واضح بالفحص السريري , بدون وجود قصة تناول صادات حيوية خلال 48 ساعة السابقة . وتم اجراء فحص بول مع زرع بول لتشخيص وجود انتان بولي عند الأطفال . النتائج : شملت عينة الدراسة 200طفلاً (60ذكرأي بنسبة 30% – 140انثى أي بنسبة 70% ) . بلغت نسبة إنتان السبيل البولي % 44 في عينة الدراسة , وكانت أكثر الحالات ضمن الفئة العمرية 5-2 سنة حيث مثلت 66% من حالات إنتان السبيل البولي وهي أعلى عند الإناث نسبة %77,3 بوجود فارق ذو قيمة إحصائية مع p-value=0.02. كانت E.coli العامل الممرض الأشيع المسبب لإنتان السبيل البولي بنسبة 63.6% وكان أكثر ملاحظة ضمن الفئة العمرية 5-2 سنة. كانت الأعراض البولية أشيع الأعراض السريرية للإنتان البولي بنسبة 30.7% وهي أعلى عند الفئة العمرية 5-2سنة , أما الأعراض الهضمية فهي أعلى عند الفئة العمرية 1شهر-2سنة بنسبة 25% من الأعراض السريرية للإنتان البولي . الاستنتاجات : تظهر الدراسة أن نسبة انتشار الإنتان البولي عند الأطفال المحمومين تحت عمر 5سنوات مرتفعة مما يستدعي تقييم الأطفال ضمن هذه الفئة العمرية من الناحية البولية بإجراء فحص بول ومع زرع ووضع العلاج المناسب لتجنب المضاعفات الخطيرة للإنتان البولي.